2020
DOI: 10.1002/mrm.28471
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 1H MRI and MRS of fatty acid composition

Abstract: Adipose tissue as well as other depots of fat (triglycerides) are increasingly being recognized as active contributors to the human function and metabolism. In addition to the fat concentration, also the fatty acid chemical composition (FAC) of the triglyceride molecules may play an important part in diseases such as obesity, insulin resistance, hepatic steatosis, osteoporosis, and cancer. MR spectroscopy and chemical-shift-encoded imaging (CSE-MRI) are established methods for non-invasive quantification of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 92 publications
(327 reference statements)
1
32
0
Order By: Relevance
“…Correction for T1 and T2 decay was performed for each resonance. For T1, data from the literature was used (Hamilton et al, 2011; Peterson et al, 2021). For T2, correction was based on the multi-echo data for the liver and on the literature for BAT and scWAT (Hamilton et al, 2011; Peterson et al, 2021).…”
Section: Methods Detailsmentioning
confidence: 99%
“…Correction for T1 and T2 decay was performed for each resonance. For T1, data from the literature was used (Hamilton et al, 2011; Peterson et al, 2021). For T2, correction was based on the multi-echo data for the liver and on the literature for BAT and scWAT (Hamilton et al, 2011; Peterson et al, 2021).…”
Section: Methods Detailsmentioning
confidence: 99%
“…It has been suggested that the degree of saturation of liver lipids may be associated with liver fat accumulation on hepatocellular damage and disease progression [ 99 , 101 ]. Each peak of lipid spectra reflects the different chemical positions within the triglyceride molecule, including unsaturated, saturated, monounsaturated, and polyunsaturated fatty acids [ 102 ]. The fatty acid composition quantification obtained from MRS has also shown good agreement with other MRI-based methods [ 103 , 104 ].…”
Section: Application Of Mrs For Liver Fat Quantificationmentioning
confidence: 99%
“…91 The theoretical basis for 1 H-MRS is underpinned by the 'chemical shift' effect whereby, when placed in a strong magnetic field, hydrogen protons within water molecules and hydrocarbon fatty acid chains resonate at different frequencies based on their surrounding chemical milieu (Figure 2A). 90 By irradiating these molecules with a radio frequency field, protons are excited and subsequently emit a signal at specific frequencies. Consequently, in a typical liver MR spectrum, water forms a large spectral peak, whilst six smaller lipid peaks are formed owing to different functional groups within a fatty acid chain (Figure 2B).…”
Section: Proton Magnetic Resonance Spectroscopy ( 1 H-mrs)mentioning
confidence: 99%